Ten years of strong opioid analgesics consumption in Malaysia and other Southeast Asian countries - Zin, Che Suraya (Wolters Kluwer - Medknow, 2020)
Background: It was reported that opioid consumption in developing countries was stagnated or decreased, but precise data on the consumption are unclear. This study examined the trends and patterns of opioid consumption in Malaysia and other four Southeast Asian countries. Materials and Methods: Data of five strong opioids consumption (morphine, oxycodone, fentanyl, pethidine, and methadone) between 2005 and 2014 from Malaysia, Singapore, Indonesia, Thailand, and Vietnam were extracted from the Pain and Policy Studies Group. Defined daily doses per 1000 inhabitants per day (DDD/1000 inhabitants/day) was used for calculating the annual amount of opioid use. Results: The total consumption of five strong opioids was increased in all five Southeast Asian countries during a 10-year study period. Malaysia was recorded with the largest increase of the opioid consumption (993.18%), followed by Indonesia (530.34%), Vietnam (170.17%), Singapore (116.16%), and Thailand (104.66%). Malaysia also had the highest total strong opioid consumption (11.2 DDD/1000 inhabitants/day), primarily for methadone. Among the opioids used for pain management, fentanyl was primarily used in Malaysia and Singapore but the greatest increase in these two countries was for oxycodone. Fentanyl was also primarily used in Indonesia while morphine was predominantly used in Thailand and Vietnam. Conclusion: Growing trends of strong opioids consumption in all five Southeast Asian countries demonstrated in this study may indicate improved access to opioid analgesics in these countries. Given the increasing trends, it is important to ensure that the utilization of opioids is according to the guideline to prevent the negative consequences of opioids particularly when used in chronic non-cancer pain.